2013
DOI: 10.3390/su5041480
|View full text |Cite
|
Sign up to set email alerts
|

CA-Markov Analysis of Constrained Coastal Urban Growth Modeling: Hua Hin Seaside City, Thailand

Abstract: Thailand, a developing country in Southeast Asia, is experiencing rapid development, particularly urban growth as a response to the expansion of the tourism industry. Hua Hin city provides an excellent example of an area where urbanization has flourished due to tourism. This study focuses on how the dynamic urban horizontal expansion of the seaside city of Hua Hin is constrained by the coast, thus making sustainability for this popular tourist destination-managing and planning for its local inhabitants, its vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 14 publications
2
60
0
Order By: Relevance
“…Although the demographic and economic data were introduced as inputs of the model already, much literature [50][51][52][53] also suggests that it will improve the good performance of the model to incorporate the population and economic growth rate for future predictions. This study considers that reason to integrate both important data to transition rate calculation through the statistical extrapolation and SD.…”
Section: Model Applicationmentioning
confidence: 99%
“…Although the demographic and economic data were introduced as inputs of the model already, much literature [50][51][52][53] also suggests that it will improve the good performance of the model to incorporate the population and economic growth rate for future predictions. This study considers that reason to integrate both important data to transition rate calculation through the statistical extrapolation and SD.…”
Section: Model Applicationmentioning
confidence: 99%
“…This larger increase of vehicles and travel time induced by infrastructure development can directly be indicative of generating accident [41], health risks such as air pollution [42], and local climate and ecological system changes [43] in the study area. Therefore, there must be According to the above analyses, it can be concluded that travel distance of local population has been associated with substantial changes in the increase of the urban area in the stage of urban formation in our study area.…”
Section: Application Of Mobility Patterns To Land Cover Changementioning
confidence: 99%
“…Finally, a Markovian process is used to allocate land for each claimants of a host class based on the derived quantity of change. The LCM has been used extensively for Reducing Emissions from Deforestation and Forest Degradation projects (REDD; e.g., [50][51][52][53]), as well as to estimate urbanization [54][55][56].…”
Section: Land Change Modelermentioning
confidence: 99%